The influence of running velocity on resultant tibial acceleration in runners - Sheerin, K. R.; Besier, T. F.; Reid, D. (Sports Biomechanics, 2020)
Tibial acceleration is a surrogate measure for impact loading and might be useful for identifying lower limb fatigue injury in runners. The resultant tibial acceleration calculated from all three axes of a triaxial accelerometer provides a single metric that is independent of the sensor orientation. The purpose of this study was to investigate the relationship between resultant tibial acceleration and running velocity, and to establish a normative database of tibial acceleration profiles. Triaxial accelerometers were attached to the distal tibiae of 85 runners before they ran on a treadmill for 2 min each, at speeds of 2.7, 3.0, 3.3, and 3.7 m/s. Differences in resultant tibial acceleration were calculated using a one-way ANOVA, and the relationship between tibial acceleration and velocity was determined using a Pearson correlation coefficient and a multiple linear regression analysis. Tibial acceleration increased with higher velocities, with an average increase of 3.8 g (38%) between the slowest and fastest speeds. A moderate correlation was demonstrated between tibial acceleration and running velocity, and 19% of tibial acceleration was explained by velocity. While velocity influences tibial acceleration, individual variances to this relationship exist, highlighting the need for a personalised approach to understanding the response of each runner.